Smallholder Farmers Contribution to Food Production in Nigeria - Chiaka, Jeffrey Chiwuikem; Zhen, Lin; Yunfeng, Hu; Xiao, Yu; Muhirwa, Fabien; Lang, Tingting (Frontiers in Nutrition, 2022)
Several studies have shown that smallholder farmers produce most of the food in low-income and developing countries and form the backbone of the country's food supply. This study examines the extent these smallholder farmers in Nigeria can put the country on the path to self-sufficiency and ensure satiety for household food consumption through their local production. The study examined food production and the resulting yield based on crop production and harvested area, as well as the percentage of crops produced for food or other purposes. The results show that production of major food crops, except for maize, is low and vulnerable, as yields of rice, sorghum, soya bean, cassava, and yam are low and declining, although harvested area increased from 2015 to 2018. In addition, the states grouped in their geopolitical zones show promising cumulative production performance when given targeted external support. As it is, the results are a clear indication of inadequate per capita food supply arising from low food production, especially for cereals. The study suggests closing the yield gap specifically for cereals, limiting post-harvest losses, and finding a sustainable balance between the uses of major food crops for animal feed to reduce pressure on land resource use. In addition, dry-season cultivation should be promoted through irrigation to enable harvesting twice in a year. The study offers useful approaches to assess the contribution of local farmers to the food supply of a growing population and provides suggestions for the government, stakeholders, and the international community willing to collaborate and invest in the agricultural sector.